Зимняя вишня: [роман] / В. И. Валуцкий - Валуцкий Владимир Иванович (Сделано в СССР. Любимая проза, 2012)
Экземпляры: аб. ЦБ (2016.13.12) / Инвентарный номер: 2694 / Цена: 100.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 15 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6